A structural model of central bank operations and bank intermediation - Ulrich Bindseil; Juliusz Jabłecki (European Central Bank (ECB), 2011)
The banking system is modeled in a closed system of financial accounts, whereby the equilibrium volume of bank intermediation between households and corporates reflects structural parameters such as household preferences, comparative cost structures of heterogeneous banks, loan demand of corporates, and the difference between the borrowing rate and the deposit facility rate of the central bank. The model also allows understanding the link between this difference (the width of the central bank standing facilities corridor) and the stance of monetary policy, and how this link changes during a financial crisis. It is shown how the narrowing of the standing facilities corridor can make more accommodating the stance of monetary policy in a financial crisis.
Keywords: E43; E44; G21; 330; bank intermediation; central bank crisis measures; central bank operations; standing facilities